Low-temperature heat capacity of fullerite C60 doped with deuteromethane - Bagatskii, M.I.; Sumarokov, V.V.; Dolbin, A.V.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The heat capacity C of fullerite doped with deuteromethane (CD4)0.4(C60) has been investigated in the temperature interval 1.2–120 K. The contribution ΔCCD4 of the CD4 molecules to the heat capacity C has been separated. It is shown that at T ≈ 120 K the rotational motion of CD4 molecules in the octahedral cavities of the C60 lattice is weakly hindered. As the temperature decreases to 80 K, the rotational motion of the CD4 molecules changes from weakly hindered rotation to libration. In the range T = 1.2–30 K ΔCCD4 is described quite accurately by the sum of contributions from the translational and librational vibrations and tunneling rotation of the CD4 molecules. The contribution of tunneling rotation to the heat capacity ΔCCD4 (T) is dominant below 5 K. The effect of nuclear-spin conversion of the CD4 molecules upon the heat capacity has been observed and the characteristic times of nuclear spin conversion between the lowest levels of the A- and T-species of the CD4 molecules at T < 5 K have been estimated. A feature observed in the curve ΔCCD4 (T) near T = 5.5 K is most likely a manifestation of a first-order phase transition in the orientational glass of the solution.